Vaginal leiomyoma: a diagnostic dilemma in vaginal mass - Bohra, Deepika; Jhirwal, Manisha; Shekhar, Shashank; Sharma, Charu; Aggarwal, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Vaginal leiomyoma is extremely rare entity. These tumours are thought to arise from Mullerian smooth muscle cells in the sub-epithelium of the vagina. Vaginal leiomyoma can occur anywhere in vaginal canal but the most common location is anterior vaginal wall. Here, we report a case of 35year old female who presented to us with mass in vagina mimicking the cystocele associated with vaginal discomfort. On clinical evaluation and preoperative imaging, it was found to be vaginal leiomyoma and it was managed surgically by enucleating the vaginal mass by giving transverse incision on anterior vaginal wall. Same mass was sent for histopathological examination which confirmed vaginal leiomyoma.